Determinants of income diversification among support zone communities of Nigeria national parks - Daniel Jacob; Samuel Onadeko; Imaobong Nelson; Abdul Shotuyo; James Ityavyar (Economic and Environmental Studies (E&ES), 2020)
This paper examined determinants of income diversification among households in support zones communities of national parks in Nigeria. This involved the use of household data collected through questionnaires administered randomly among 1009 household heads in the study area. The data obtained were analyzed using probability and non-probability statistical analysis such as regression and analysis of variance to te st for mean difference between parks. The result obtained indicates that the majority of household heads were male (92.57% between the age group of 21-40 years (44.90%), had non-formal education (38.16%), were farmers (65.21%), owned land (95.44%), with the household size of 1-5 (36.67%) and an annual income range of ₦401,000 - ₦600,000 (24.58%). Mean Simpson index of diversity showed a general low (0.375) level of income diversification among the households. Income, age, off-farm dependence, education, household size and occupation where significant (p<0.01) factors that affected households' income diversification. The study recommends improvement in the existing infrastructures and social capital in the communities as avenues to improve the livelihood and ensure positive conservation behaviors in the study area.
Keywords: Q56; Q57; Q58; 330; Income diversification; Protected area; Livelihood; Poverty; Nigeria